Control of development: role of regulatory nucleotides synthesized by membranes of Bacillus subtilis in initiation of sporulation. - Rhaese, H J (1976)
A model explaining the mechanism of initiation of differentiation is presented. It is based on the finding that sporulation in B. subtilis can be induced by the same nutrient deficiencies that also induce the synthesis of highly phosphorylated nucleotides. Two of these nucleotides are synthesized by membrane vesicles. Synthesis can be inhibited by the same metabolites of glucose that also inhibit sporulation. It is concluded, therefore, that the plasma membrane synthesizes unusual nucleotides in response to nutrient deficiencies. By several as yet unknown steps, these nucleotides then cuase changes in the metabolism of the organism leading to the formation of spores. Both structure and mechanism of synthesis of adenosine hexaphosphate, pppAppp, have been elucidated by use of ATP analogues.